Effect of Health Education Regarding Awareness Examination as Early Detection of Breast Cancer on the Knowledge and Attitude of Adolescent Women at the Medan Tuntungan Health Center - Rochmawati, Arva; Anggraini, Desi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Breast cancer (Carsionama mamae) is cancer that originates from the glands, ducts and supporting tissues of the breast but does not include the skin of the breast. Breast cancer is the second most common cancer affecting Indonesian women and is the number one killer of women in the world (Mangan, 2005). The purpose of this study was to find the effect of education between health education regarding BSE examination and the knowledge and attitudes of young women at the Medan Tuntungan Health Center in 2020. The research method used was quasi-experimental. The population in this study were all young women who lived in the area of ​​the Medan Tuntungan Health Center. Sampling technique with a total sampling of 34 people. The results of statistical tests using the Wilcoxon test, obtained p value = 0.025 (p value <0.05) meaning Ho is rejected, which means that there is an influence between the Health Department on adolescent attitudes about BSE examinations. It is hoped that adolescents can increase their knowledge about BSE examinations and be more concerned with their own health conditions so that they can detect cancer in themselves early.